Exposure to cuticular bacteria can alter host behavior in a funnel-weaving spider. Issue 6 (16th November 2017) - Parks, Olivia B; Kothamasu, Krishna S; Ziemba, Michael J; Benner, Morgan; Cristinziano, Madison; Kantz, Serena; Leger, Daniel; Li, John; Patel, Devanshi; Rabuse, William; Sutton, Samantha; Wilson, Amandi; et al.
Abstract: Contact with environmental microbes are arguably the most common species interaction in which any animal participates. Studies have noted diverse relationships between hosts and resident microbes, which can have strong consequences for host development, physiology, and behavior. Many of these studies focus specifically on pathogens or beneficial microbes, while the benign microbes, of which the majority of bacteria could be described, are often ignored. Here, we explore the nature of the relationships between the grass spider Agelenopsis pennsylvanica and bacteria collected from their cuticles in situ . First, using culture-based methods, we identified a portion of the cuticular bacterial communities that are naturally associated with these spiders. Then, we topically exposed spiders to a subset of these bacterial monocultures to estimate how bacterial exposure may alter 3 host behavioral traits: boldness, aggressiveness, and activity level. We conducted these behavioral assays 3 times before and 3 times after topical application, and compared the changes observed in each trait with spiders that were exposed to a sterile control treatment. We identified 9 species of bacteria from the cuticles of 36 spiders and exposed groups of 20 spiders to 1 of 4 species of cuticular bacteria. We found that exposure to Dermacoccus nishinomiyaensis and Staphylococcus saprophyticus was associated with a 10-fold decrease in the foraging aggressiveness of spiders toward prey in their web. Since bacterial exposure did not have survival consequences for hosts, these data suggest that interactions with cuticular bacteria, even non-pathogenic bacteria, could alter host behavior.